The Development of Procedural Law Through the E-Court System After Pandemic in Indonesia - herina wati; Tan Kamello; Marlia Sastro (Veteran Law Review, 2023)
Technological developments and Covid 19 Pandemic "forced" the Supreme Court (MA) to make breakthrough in procedural law, namely by launching E-Court application, through MA rules Number 3 of 2018 which was exchanged for rules Number 1 of 2019 concerning Case Administration and Trial in E-Courts. E-Court is instrument in court for service of case registration depositing case money to court summons and trial and online delivery of court documents. This study aims to analyze and provide an overview to public of breakthroughs made by the MA for Development of Procedural Law through e-court system. Research method used qualitative research, normative juridical approach. The development of procedural law was initially only intended for registration and examination of civil cases through Supreme Court rules (Perma) No. 3 of 2018 was replaced with Perma No. 1 of 2019 concerning Case Administration and Trial in Electronic Courts. But then e-court is not only for civil cases, it’s also to adjudicate criminal cases with issuance of MA regarding the online criminal trial file Number 4 of 2020. The application for electronic proceedings is an attempt by the Supreme Court to eliminate the obstacles commonly experienced by the judiciary, namely the lack of speed in resolving cases, the difficulty of obtaining data from the court, and the credibility of the integrity of the judiciary, especially judges